Celtic mythology - Mac Cana, Proinsias (New York : P. Bedrick Books, 1985)
Describes the gods, myths, and epic legends of the Celts, discussing their sources, their relationship with Celtic history, and the influence of the Romans.
Includes index.
Bibliography: p. 140.
Keywords: Gods, Celtic; Mythology, Celtic; Celts